Quality of Life Assessment in Patients Using Benzodiazepines during the COVID-19 Pandemic in a Community Pharmacy Using EuroQol 5D-3L - Daida Alberto Armas; Juan Ramón Santana Ayala; Yanira Román Castillo; Arturo Hardisson de la Torre; Carmen Rubio Armendáriz (MDPI AG, 2023)
Users of benzodiazepines (BZDs) should have their quality of life monitored to minimize the risks associated with long-term treatments. The aim of this study is to use the EuroQol 5D-3L to analyze the quality of life of 127 patients under treatment with BZDs during the COVID-19 pandemic. The results show that lorazepam comprises 25.49% of all dispensing requests, and that the mean duration of BZDs treatments is four years (range: 0.3-25). When rating their general health status, BZDs users reported 59.29 points out of 100. Thirty-two percent of patients reported mobility problems; 16.5% reported having a lot of pain or discomfort despite being treated with BZDs, and 16.54% used a BZD together with an opioid analgesic. The EuroQol 5D-3L dimension "anxiety/depression" showed that, despite the use of BZDs, 48.2% of the patients reported being moderately anxious or depressed and 13.4% described themselves as very anxious or depressed. Nevertheless, 37.8% of BZDs users were identified as potential candidates to follow a BZD deprescription plan. In conclusion, BZDs users showed a low quality of life during the COVID-19 pandemic. Older patients and females have been identified as groups of patients that could benefit from integrating the use of the EuroQol 5D-3L instrument into the protocols of the pharmaceutical care follow up.